The slowdown in German bank lending - revisited - Thorsten Polleit (Hochschule für Bankwirtschaft (HfB), 2004)
The rate of growth in bank loans to private households and firms in Germany has declined substantially since early 2000 and currently stands at virtually zero. In this article, we analyse whether cyclical factors ('demand-side driven') or banks' unwillingness and/or inability to lend ('supply-side driven') can be held responsible for this trend.Our preliminary results suggest that the slowdown in bank loan expansion is largely driven by a decline in the demand for loans. This result is supported by taking into account the latest tendency of corporates substituting bank loans for the issuance of money and capital market instruments. Although it cannot be ruled out that supply-side restrictions have contributed to the dampening of real bank loan expansion, to date these factors have played only a minor role.
urn:nbn:de:101:1-20080724117
Keywords: G20; G21; 330; German bank lending; Credit rationing